When Tiger Mothers Meet Sugar Sisters: Strategic Representations of Chinese Cultural Elements in Maxine Hong Kingston's and Amy Tan's Works - Huang, Sheng (Curtin University, 2017)
This thesis examines how Maxine Hong Kingston and Amy Tan use Chinese cultural elements as strategies to challenge stereotypes of Chinese Americans in the United States. The project combines literary and cultural studies approaches to explore how these Chinese elements in the two authors’ works interact with mainstream U.S. culture. This strategy enables Kingston and Tan to articulate resistance against racism and open new spaces for later writers, although it might also risk reinforcing stereotypes.